Passivity control in multilevel cascaded H-bridge converters : a variable gain approach - Rodriguez, Ezequiel (2020)
This paper proposes a multi-input linear time-variant control law based on the incremental passivity theory for cascaded H-bridge (CHB) low-capacitance static compensators (LC-StatComs). The proposed control law guarantees global asymptotic stability of the system and controls the capacitor voltages and inductor current without assuming fast dynamics in the current and slow dynamics in voltages. This is particularly important for LC-StatCom applications as the control of the inductor current and capacitor voltages are inherently coupled due to the reduced capacitance. After introducing the incremental model of the converter, a passivity-based control that ensures the global stability is derived. Simulation results on a seven-level 1-kVA CHB LC-StatCom are shown to corroborate its excellent performance in steady-state and during transients.